Factors associated with neonatal deaths in Chitwan district of Nepal. (December 2015) - Shah, Rajani; Sharma, Bimala; Khanal, Vishnu; Pandey, Usha; Vishwokarma, Anu; Malla, Dinesh
Abstract Background Neonatal mortality has remained unchanged since 2006 in Nepal. Reducing neonatal mortality is indispensable to reduce child mortality. The objective of this study was to investigate the factors associated with neonatal mortality. This study assesses socio-demographic factors, maternal health care and newborn care practices contributing to neonatal deaths in Chitwan district of Central Nepal. Methods A case–control study was conducted during April–July 2012. The study used a mixed-method approach, in which records of neonatal deaths were obtained from the District Public Health Office and a comparison group, survivors, was obtained from the same community. A total of 198 mothers (of 99 neonatal deaths and 99 survivor neonates) were included in the survey. Focus group discussions, in-depth interviews and case studies were also conducted. Maternal characteristics were analyzed using descriptive statistics, Mc Nemar's Chi square test and multivariable backward conditional logistic regression analysis. Qualitative data were analyzed by narrative analysis method. Results More than four-fifth of mothers (86 %) had antenatal check-up (ANC) and the proportion of four or more ANC was 64 %. Similarly, the percentage of mothers having institutional delivery was 62 %, and postnatal check-up was received by 65 % of mothers. In multivariable analysis, low birth weight [adjusted odds ratio: 8.49, 95 % CI (3.21–22.47)], applying nothing on cord [adjusted odds ratio: 5.72, 95 % CI (1.01-32.30)], not wrapping of newborn [adjusted odds ratio: 9.54, 95 % CI (2.03–44.73)], and no schooling of mother [adjusted odds ratio: 2.09, 95 % CI (1.07–4.11)] were significantly associated with an increased likelihood of neonatal mortality after adjusting for other confounding variables. Qualitative findings suggested that bathing newborns after 24 h and wrapping in clean clothes were common newborn care practices. The mothers only attended postnatal care services if health problems appeared either in the mother or in the child. Conclusion Results of this study suggest that the current community based newborn survival intervention should provide an even greater focus to essential newborn care practices, low birth weight newborns, and female education.